Multicomponent Solids of Niflumic and Mefenamic Acids Based on Acid-Pyridine Synthon - Kumar, Vineet; Goswami, Pramod Kumar; Balendra,; Tewari, Shailabh; Ramanan, Arunachalam (Frontiers in Chemistry, 2022)
The present study discusses comparative structural features of fourteen multicomponent solids based on two nonsteroidal anti-inflammatory drugs, Niflumic and Mefenamic acids with amine and pyridine-based coformers. All the solids were structurally characterized through PXRD, SCXRD, DSC, and the monophasic nature of some of the solids was established through Rietveld refinement. The solid forms include salt, cocrystal, salt-polymorphs, hydrates, and solvates. All the reported solids, except two, showed significant improvement in solubility in comparison to the acids. A difference in pKa of both the molecules with similar structural features enabled us to systematically understand the influence of ΔpKa on the outcome of crystallization. The structural chemistry of all the solids is discussed through the perspective of acid∙∙∙pyridine synthon.